2021
DOI: 10.1080/15685551.2021.1984008
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and in vivo/in vitro characterization of Ticagrelor PLGA sustained-release microspheres for injection

Abstract: The objective of this paper was to develop a PLGA carrier Ticagrelor sustained-release microspheres preparation, which was expected to continue to release Ticagrelor for 14 days with a high encapsulation rate. Ticagrelor microspheres were prepared successfully with average diameter of 7.31 µm, drug loading of 12.49 ± 0.32% and EE up to 79.09 ± 1.69%. In the release medium of PH7.4 PBS, the microspheres showed good drug release behavior in vitro. In vivo release results also showed that the sustained-release mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The biocompatible microsphere was suggested for long-term treatment of acute coronary syndrome. 64 However, the non-oral delivery system was designed for injection with low loading capacity. Zaman et al have used a thiolated hemicellulose as a muco-adhesive pharmaceutical excipient for formulation of Ticagrelor tablet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biocompatible microsphere was suggested for long-term treatment of acute coronary syndrome. 64 However, the non-oral delivery system was designed for injection with low loading capacity. Zaman et al have used a thiolated hemicellulose as a muco-adhesive pharmaceutical excipient for formulation of Ticagrelor tablet.…”
Section: Discussionmentioning
confidence: 99%
“…Linkun Hao et al developed an injectable PLGA‐based microsphere which showed sustained release trend in in vitro and in vivo. The biocompatible microsphere was suggested for long‐term treatment of acute coronary syndrome 64 . However, the non‐oral delivery system was designed for injection with low loading capacity.…”
Section: Discussionmentioning
confidence: 99%
“…PLGA microspheres with sustained release can help to achieve long-term effects of drugs, shorten drug administration time and reduce the fluctuation of drug concentration in the blood [ 241 ]. In a study, PLGA microspheres encapsulated with AG were developed with significant sustained release property.…”
Section: Other Aspects Of Agmentioning
confidence: 99%